Discovery and optimization of a novel series of highly CNS penetrant M4 PAMs based on a 5, 6-dimethyl-4-(piperidin-1-yl)thieno[2, 3-d]pyrimidine core. Issue 13 (1st July 2016) - Wood, Michael R.; Noetzel, Meredith J.; Engers, Julie L.; Bollinger, Katrina A.; Melancon, Bruce J.; Tarr, James C.; Han, Changho; West, Mary; Gregro, Alison R.; Lamsal, Atin; Chang, Sichen; Ajmera, Sonia; et al.
Graphical abstract: Abstract: This Letter describes the chemical optimization of a novel series of M4 positive allosteric modulators (PAMs) based on a 5, 6-dimethyl-4-(piperidin-1-yl)thieno[2, 3- d ]pyrimidine core, identified from an MLPCN functional high-throughput screen. The HTS hit was potent and selective, but not CNS penetrant. Potency was maintained, while CNS penetration was improved (rat brain:plasma K p  = 0.74), within the original core after several rounds of optimization; however, the thieno[2, 3- d ]pyrimidine core was subject to extensive oxidative metabolism. Ultimately, we identified a 6-fluoroquinazoline core replacement that afforded good M4 PAM potency, muscarinic receptor subtype selectivity and CNS penetration (rat brain:plasma K p  > 10). Moreover, this campaign provided fundamentally distinct M4 PAM chemotypes, greatly expanding the available structural diversity for this exciting CNS target.